Condom use among HIV sero-concordant couples attending a secondary health facility in North-Central Nigeria - Salaudeen, A. G.; Ojotule, A.; Durowade, K. A.; Musa, O. I.; Yusuf, A. S.; Saka, M. J. (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: Condom use during intercourse is perceived as unnecessary in sexual encounters involving a regular partner. The non-use of condom among HIV-positive people has been found to increase the risk of resistance to anti-retroviral therapy. The objective of this study was to determine the pattern of condom use among HIV sero-concordant couples attending a secondary health facility in North-Central Nigeria. Materials and Methods: This is a cross-sectional survey that was carried out among people living with HIV and AIDS (PLWHA) who have been enrolled into care and treatment at General Hospital Abejukolo in Kogi State, Nigeria. The data instrument used was self-/interviewer-administered questionnaire. The data obtained were analysed using EPI-INFO version 3.4.1 software package. Chi-square test was used andP< 0.05 was considered significant for the study. Results: Assessment of knowledge of the respondents on the correct use of condom showed that two-thirds (60; 65.9%) had good knowledge and 70 (79.6%) of them demonstrated positive attitude towards the use of condom during sexual intercourse. About one-third of the respondents (32; 35.2%) would oblige the spouse sexual intercourse without condom mainly because they are both positive, to fulfil marital obligations and to avoid problems in marital relationship. Less than two-thirds (59.3%) of sero-concordant spouse used condom during sexual intercourse for reasons of preventing re-infection and pregnancy. Conclusion: With one-third of respondents not using condom during sexual intercourse, there is a great challenge for spread of HIV infection and risk of drug resistance in HIV care and management. Therefore, stakeholders at various levels should intensify efforts and support research towards behavioural modification in addressing the existing lacunae in HIV control.